Assessing the projected impacts of alternative PSTA5 spending trajectories on the Rwandan economy - Aragie, Emerta A.; Ingabire, Chantal; Knudsen, Mads; Thurlow, James; Warner, James (International Food Policy Research Institute, 2025)
Data-driven and evidence-based approaches are critical for shaping public policy, investment, and expenditure decisions, ensuring that development plans are effective and well-informed. The RIAPA model, utilized in this study, has played a key role in informing policy discussions, including the identification of national priorities and strategies, the mid-term assessment of the Rwanda’s fourth Strategic Plan for Agriculture Transformation (PSTA 4), and the post-COVID-19 recovery and relief efforts. This policy note employs a Rwanda-specific RIAPA model integrated with an investment module to analyze the expected benefits from agricultural investments outlined in the Fifth Strategic Plan for Agriculture Transformation (PSTA 5) for 2025-2029. Results show that, compared to PSTA 4 spending trends, a moderate spending scenario under PSTA 5 could accelerate agricultural transformation and inclusive growth by 2.8 percentage points. A higher budget scenario, re quiring an average annual expenditure of $610 million, is projected to reach an ambitious eight percent agricultural growth target. Faster agricultural growth would further stimulate the off-farm components of the agri-food system, reinforcing agriculture's role as an economic growth engine. By 2029, PSTA 5 could reduce poverty and undernourishment by 1.6 million people, contingent on managing potentially significant climatic and external economic risks.